2013
DOI: 10.1016/j.mayocp.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations and Emergency Department Use in Mayo Clinic Biobank Participants Within the Employee and Community Health Medical Home

Abstract: Objective To evaluate the participants in the Mayo Clinic Biobank for their representativeness to the entire Employee and Community Health (ECH) primary care population with regards to hospital utilization. Patient and Methods Participants enrolled in the Mayo Clinic Biobank from April 1, 2009, to December 31, 2010, were linked to ECH panels. Subjects were categorized into risk tiers (0–4) based on the number of health conditions as of December 31, 2010. Outcomes were ascertained through December 31, 2011. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…HOUSES may not completely represent SES because SES is a multifactorial classification. Our cohort was derived from the MCB and may not reflect a population-based sample, and may reflect some selection bias 22. In addition, Olmsted County tends to have a greater white population and higher education levels than counties nationwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOUSES may not completely represent SES because SES is a multifactorial classification. Our cohort was derived from the MCB and may not reflect a population-based sample, and may reflect some selection bias 22. In addition, Olmsted County tends to have a greater white population and higher education levels than counties nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…This study enrolled all eligible adult Mayo Clinic primary care patients who were enrolled voluntarily in the Mayo Clinic Biobank (MCB)21 and were residents of Olmsted County, Minnesota, USA 22. We limited our study patients to MCB participants living in Olmsted County at the time of MCB enrolment because HOUSES is available to the Olmsted County population only.…”
Section: Methodsmentioning
confidence: 99%
“…Our findings suggest that healthcare providers may need to account for comorbid health burden and age for interpretation. HRQOL outcomes may need to be reported by different age category or by different comorbid health burden like Minnesota Medical Tier [ 25 ]. Categorizing both groups may allow accurate comparison of HRQOL which is not dependent on different comorbid health burden.…”
Section: Discussionmentioning
confidence: 99%
“…All participants from the study were from the Mayo Clinic Biobank (MCB). The MCB is an institutional resource initiated by the Mayo Clinic Center for Individualized Medicine [ 23 25 ]. Enrollment into the MCB began in April 2009 and is ongoing with a target goal of 50,000 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Various aspects of the Mayo Clinic Biobank population have been described earlier 6–10. Takahashi et al 11 helped us understand our participants by comparing participants in the Mayo Clinic Biobank who were assigned a primary care provider in Rochester, Minnesota (39% at time of publication) to the entire Rochester primary care (Employee and Community Health, ECH) population. We found that Biobank patients were older and had more chronic conditions than the underlying ECH population overall.…”
Section: Findings To Datementioning
confidence: 99%